M04 European huntington's disease network registry: current status. (29th August 2012) - Handley, O; Landwehrmeyer, B
Abstract : Background: The European Huntington's disease Network's (EHDN) REGISTRY is an observational, prospective, longitudinal, multi-national, multi-centre cohort study of Huntington's disease (HD). It is the largest study of HD to date, and collects valuable phenotypical data and biospecimens on individuals who are at risk of, premanifest or manifest for HD, and includes control participants and non-expansion mutation carriers. Aims: Registry aims to establish a well-characterised European-based HD population to expedite high-quality research to improve our knowledge of this disease and to work towards discovering and developing therapies to delay or slow HD. Methods/techniques: Registry follows a prospective study design, with participants attending annual visits. Pseudonymised clinical data are stored centrally on a customised webportal (http://www.euro-hd.net/Registr y). Biospecimens are processed and stored centrally at BioRep, Milan, Italy. All data are captured online and are subject to regular quality control checks for plausibility and accuracy. Three Registry sub-studies (Juvenile HD, Physiotherapy and Lifestyle) have been active in multiple study sites since 2011. Results/outcome: Registry data have been collected from 17 European countries. Over 9000 participants have contributed phenotypical data, and of those, more than 6000 participants have contributed biosamples for further use in large-scale genetic modifier and biomarker HD studies. On average, 100 participants are enrolled into Registry each month, and approximately 250 biospecimens (including resubmissions from existing participants) are submitted. A summary of the key study metrics including demographics and disease stage of the Registry cohort and an overview of substudy enrolment figures are presented. Conclusions: Registry has been successful in establishing a well-characterised European-based HD cohort. The study protocol was amended in 2009 to include retrospective data collection (pre-enrolment to Registry), video-recording, and the development and validation of novel/additional endpoints for therapeutic interventions. To date, a total of 60 data mining proposals have been approved access to the Registry database. The study has expedited the coordination and implementation of clinical trials of promising compounds and has proven successful in expediting substudies and regular data collection.